Feeling anxious and abusing low performers: A multilevel model of high performance work systems and abusive supervision. (26th August 2021) - Xi, Meng; He, Wei; Fehr, Ryan; Zhao, Shuming
Summary: In the present research, we identify high performance work systems (HPWSs) as an important yet unexamined driver of abusive supervision. Drawing from the theory of workplace anxiety, we specifically propose that HPWSs increase leader anxiety, especially when the leader's job experience is relatively low. Then, we argue that this anxiety ultimately causes leaders to abuse their employees in response, especially when those employees are poor performers. We tested our hypotheses in a field study (Study 1) using multiwave, multisource, multilevel data collected from 508 employees nested in 81 departments across 24 organizations in China and in a sample of US managers (Study 2) that also examined alternative explanations for our effects. Taken together, our findings offer new insight into the cross‐level drivers of abusive supervision and highlight the critical role of emotion in the link between human resource (HR) systems and leader behavior.